Il cibo che mangi(amo): gli zuccheri: Metodologie cooperative per supportare la corretta nutrizione nella Scuola Primaria - Bertinetto, Luisa; Turco, Francesca (Chimica nella Scuola, 2024)
This article reports a fragment of the activities carried out in the Experimental Thesis path proposed in two fourth classes of the Primary School. Thanks to this path, the adoption of proper nutrition is promoted, making use of an Experiential Laboratory and cooperative teaching methodologies, capable of privileging the collective construction of knowledge. The field of Food Education is extensively explored, starting with the dimension “Me and food”, continuing with “Me, food and eating habits” and ending with “Me, food and the environment”. The part of the pathway described in detail here concerns eating habits, with a focus on sugar.